“This Is Something That Changed My Life”: A Qualitative Study of Patients' Experiences in a Clinical Trial of Ketamine Treatment for Alcohol Use Disorders - Mollaahmetoglu, O. Merve; Keeler, Johanna; Ashbullby, Katherine J.; Ketzitzidou-Argyri, Eirini; Grabski, Meryem; Morgan, Celia J. A. (Frontiers in Psychiatry, 2021)
Background: The therapeutic benefits of ketamine have been demonstrated for a variety of psychiatric disorders. However, the role of ketamine induced psychoactive experiences in mediating the therapeutic effects is unclear. Despite the growing quantitative research on the efficacy of ketamine treatment, very few studies examined participant experiences of ketamine infusions in a treatment setting. Aims: The current study aimed to examine participant experiences of ketamine infusions and how these relate to therapeutic mechanisms in a clinical trial setting. Methods: We conducted semi-structured interviews with 12 participants who received up to three ketamine infusions (0.8mg/kg) as part of a Phase II double blind, randomised controlled trial. The interviews explored participants’ acute experiences of ketamine infusions, experiences of psychotherapy/education, and the lasting effects of the trial. The interviews were transcribed verbatim and analysed using thematic analysis. Results: Four Six key themes were identified. 1) Participants reported: the multifaceted motivations for trial participation., 2) The set and setting as was found to be influential in determining acute ketamine experiences. The acute ketamine experiences included ,3) the inherent contradictions of the experience (e.g. dissociation vs feelings of connection), 4) rapidly fluctuating and changing experiences, 5) meaning, mystical and spiritual experiences.of the acute ketamine experience, and Finally, the final theme relates to the transformational effects of the the infusions and/the trialrial having potentially transformational effects. Conclusion: Provided in a supportive and professional environment, ketamine treatment can leadled to a significant change in relationship with alcohol. Ketamine induced ego dissolution and dissociation were reported to be related to the transformational effects on relationship with alcohol, Whilst ego dissolution and dissociation were related to transformational changes here, Tthe extent to which the acute psychoactive effects of ketamine mediate its therapeutic effects on drinking outcomes remain to be fully investigated in the trial data. The acute effects of ketamine reported by our participants transcend its traditional conceptualisation as a “dissociative anaesthetic”; therefore, we suggest the development or use of new measures alongside ketamine infusions to fully capture the spectrum of these effects which may be crucial in its therapeutic and transformative effects.